Relationship of Mother Knowledge about Contraceptive Pills and Compliance the Use of Contraceptive Pills in Medan Tuntungan - Nurdiana Manurung; Rizky Andriani Bakara (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Knowledge is the result of